The Influence of Information Technology, Organizational Culture, and Digital Competence on Worker Job Satisfaction in the Special Region of Yogyakarta: inggris - Fatra, Nargadias; Kurniawan, Ignatius Soni; Kusuma, Nala Tri (STIE Indonesia Banking School, 2025)
Advances in information technology, adaptive organizational culture, and employee digital competence are important factors in determining the level of job satisfaction in the digital era. The purpose of this study is to examine how employee work satisfaction in the Special Region of Yogyakarta (DIY) is impacted by digital competency, organizational culture, and information technology. This study used a quantitative approach with an accidental sampling technique, resulting in a total of 101 respondents from both the private and non-private sectors. Data were collected through a Google Form-based questionnaire and analyzed using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method using SmartPLS 3.0 software. The results show that information technology has a positive and significant effect on job satisfaction, organizational culture has a favorable and large impact on job satisfaction, and job contentment is positively and significantly impacted by digital competence as well. Thus, the effective implementation of information technology, a positive organizational culture, and improving employee digital competence have been proven to make a significant contribution to increasing job satisfaction. Organizations are expected to strengthen a conducive work culture and develop continuous digital competence training to support employee productivity and well-being in the era of digital transformation.